EFFECT OF ENDORSER CREDIBILITY, BRAND CREDIBILITY, SELF-BRAND CONNECTION ON BRAND EQUITY - Rowlan Takaya (Universitas Trisakti, 2018)
Purpose – The purpose of this research was to study the impact of endorser credibility, brand credibility, self-brand connection on endorsed brand equity of the endorsed brand.Design/methodology/approach - The analytical method using Amos 24 and Structural Equation Modeling (SEM) to analyze the questionnaire data in Jakarta. There are 417 eligible questionnaires were analyzed.Findings – To study the effect of endorser credibility on brand credibility, endorser credibility to brand equity, brand credibility to brand equity, endorser credibility to self-brand connection and self brand connetion to brand equity.Research limitation – The research was based in this study using college student customer of Vivo Smartphone at Jakarta as a research object.Research implication – Managers can consider using celebrities as a tool to develop meaningful connectivity connections with consumers. The results of this study support the use of celebrity endorsers as a means of increasing brand equity directly.Originality/value – This study examines the impact of celebrity endorsers in delivering, influencing, and depicting the product significantly so that consumers buy the product, so that the target marketing made through the endoser can be achieved.